Proposal of model for creating innovation strategy - Lendel, Viliam; Varmus, Michal (Univerzita Pardubice, 2010)
The process of creating an innovation strategy is a complex process. The contribution deals with the process of creating an innovation strategy. It gives new insights in analysis of environment and strategy formulation. The contribution provides a comprehensive look at the creation of innovative strategies using elements of the proposed expert system. Part of the article is also recommendations for successful implementation of innovative strategy in the enterprise.
Keywords: innovation strategy; expert system; innovation; management; innovative potential; strategic management